TWEAK-Fn14 Cytokine-Receptor Axis: A New Player of Myocardial Remodeling and Cardiac Failure - Novoyatleva, Tatyana; Sajjad, Amna; Engel, Felix B. (Frontiers in Immunology, 2014)
Tumor necrosis factor (TNF) has been firmly established as a pathogenic factor in heart failure, a significant socio-economic burden. In this review we will explore the role of other members of the TNF/TNF receptor superfamily (TNFSF/TNFRSF) in cardiovascular diseases (CVDs) focusing on TWEAK and its receptor Fn14, new players in myocardial remodeling and heart failure. The TWEAK/Fn14 pathway controls a variety of cellular activities such as proliferation, differentiation and apoptosis and has diverse biological functions in pathological mechanisms like inflammation and fibrosis that are associated with CVDs. Furthermore, it has recently been shown that the TWEAK/Fn14 axis is a positive regulator of cardiac hypertrophy and that deletion of Fn14 receptor protects from right heart fibrosis and dysfunction. We discuss the potential use of the TWEAK/Fn14 axis as biomarker for CVDs as well as therapeutic target for future treatment of human heart failure based on supporting data from animal models and in vitro studies. Collectively, existing data strongly suggest the TWEAK/Fn14 axis as a potential new therapeutic target for achieving cardiac protection in patients with CVDs.